Mastering desktop publishing - Mitchell, Simon (Macmillan master series, 1999)
If you design to publish on a computer, in print or digital media, then this book is an essential resource. Both the quality and effectiveness of your work will improve through focus on design. This easy-to-follow book describes processes and tools available for successful desktop publishing (DTP), backed up with over two hundred illustrations. It reveals the tricks, secrets and magic ingredients for design in desktop publishing. Recommended for 'in-house' DTP and those studying: 7 communications 7 media 7 business 7 marketing 7 design 7 desktop publishing Mastering Desktop Publishing offers the reader techniques, skills and strategies to achieve effective results in publishing.